2020
DOI: 10.1080/09553002.2020.1793015
|View full text |Cite
|
Sign up to set email alerts
|

NRP1 regulates radiation-induced EMT via TGF-β/Smad signaling in lung adenocarcinoma cells

Abstract: Purpose: Radiation has been shown to promote the epithelial-mesenchymal transition (EMT) in tumor cells, and TGF-b/Smad and PI3K-Akt signaling pathways play an important role in the EMT. In this study, we investigated the effects of neuropilin-1 (NRP1) on radiation-induced TGF-b/Smad and non-classical Smad signaling pathways in lung cancer cells, as well as the effects of NRP1 on invasion and migration. Materials and methods: Changes in the expression levels of EMT markers (b-catenin, N-cadherin, and vimentin)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Neuropilin-1 may promote EMT induced by radiation via TGF-β1/Smad2/3 signaling in lung cancer cells and thus enhance invasion and migration. 27 Furthermore, we knocked down Smad2 in OC cells to explore whether TGF-β1 treatment-induced changes in the EMT markers such as E-cadherin and vimentin expression in OC cells occurred through the KLF8/ Smad2 axis. Our findings indicate that expression of E-cadherin was increased, KLF8 and vimentin expression was reduced in Smad2-deficient cells, and TGF-β1 induction failed to induce KLF8 expression and EMT in Smad2-deficient cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropilin-1 may promote EMT induced by radiation via TGF-β1/Smad2/3 signaling in lung cancer cells and thus enhance invasion and migration. 27 Furthermore, we knocked down Smad2 in OC cells to explore whether TGF-β1 treatment-induced changes in the EMT markers such as E-cadherin and vimentin expression in OC cells occurred through the KLF8/ Smad2 axis. Our findings indicate that expression of E-cadherin was increased, KLF8 and vimentin expression was reduced in Smad2-deficient cells, and TGF-β1 induction failed to induce KLF8 expression and EMT in Smad2-deficient cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies reported TGF‐β1‐induced EMT transcription and regulation of E‐cadherin, vimentin, N ‐cadherin, Snail, and support cancer progression. Neuropilin‐1 may promote EMT induced by radiation via TGF‐β1/Smad2/3 signaling in lung cancer cells and thus enhance invasion and migration 27 …”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, Nrp1 is reported as a new tumor marker in hepatocellular carcinoma 20 ; it also regulates gastric cancer progression 21 and enhances the invasive and migratory properties of lung adenocarcinoma cells. 22 The INHBA gene plays an important role in many tumors, with high INHBA levels in esophageal squamous cell carcinoma and other solid tumors reflecting poor prognosis. 23 Moreover, INHBA overexpression results in poor clinical outcomes in bladder urothelial carcinoma, indicating its potential as a prognostic marker and a new therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of cells to ionizing radiation determines the efficacy of radiotherapy, and the inherent radioresistant ability of tumour cells further limits the use of radiotherapy (3). NRP1 can enhance the radiation resistance of tumours (8,9,30,31). Previous studies have shown that the expression of NRP1 significantly increases with increasing radiation dose.…”
Section: Discussionmentioning
confidence: 99%